Courts, Legitimacy and the Rule of Law. Issue 3 (16th October 2017) - Fatima, Shaheed
Abstract : The role of courts as lawmakers has been scrutinised, partly because of the questions it raises regarding legitimacy. This scrutiny has sometimes assumed that courts are safe from legitimacy-based criticism in their role as appliers of law. However, recent events in the United Kingdom show that, regrettably, this is not so: the media reaction to the judgments in the Brexit case of Miller went far beyond criticism of the courts' reasoning or conclusions. It was an attack on legitimacy. Insofar as such attacks arise out of misunderstandings about the nature of adjudication (including, for example, the existence and scope of judicial discretion), one way of countering them is for the legal community (scholars, judges, practitioners) to continue to increase public awareness about these issues. However, it is incumbent upon other parts of the state – the executive and the legislature – to respond promptly to such attacks in order to uphold the independence of the judiciary and the rule of law.